Genome-Wide Identification of the HD-ZIP III Subfamily in Upland Cotton Reveals the Involvement of GhHB8-5D in the Biosynthesis of Secondary Wall in Fiber and Drought Resistance - Zhang, Jie; Gao, Yanan; Feng, Mengru; Cui, Yuke; Li, Shuaijie; Liu, Le; Wang, Ye; Xu, Wenliang; Li, Fuguang (Frontiers in Plant Science, 2022)
The thickness of cotton fiber secondary wall determines the fiber quality. HD-ZIP III transcription factors play distinct roles in the secondary wall biosynthesis. However, little is known regarding the function of HD-ZIP III subfamily in cotton fiber secondary wall deposition. In this study, 18 HD-ZIP III genes were identified and they distributed on 14 chromosomes in cotton genome. All of them have undergone segmental duplication. Moreover, many cis-elements in the promoter regions of these 18 GhHD-ZIP III genes were related to phytohormone responsive and abiotic stresses. qRT-PCR results showed that they were expressed in different cotton tissues and GhHB8-5D was preferentially expressed in fibers. GhHB8-5D protein was demonstrated to be targeted to the cell nucleus and had self-activation ability. In addition, expression of GhHB8-5D and GhHB8-5Dm in Arabidopsis resulted in short and small plants, curly leaves and twisted inflorescence stems. Furthermore, the morphology of vascular bundles and deposition of secondary wall had changed in overexpressed stems. The transcription levels of secondary wall related genes were also significantly altered in transgenic Arabidopsis. Very interestingly, expression of GhHB8-5D and GhHB8-5Dm in Arabidopsis displayed higher green seedling rate and shorter root length than those of the wild type on MS medium containing mannitol. Taken together, our results shed new light on the roles of GhHB8-5D and reveal cell wall changes in response to abiotic stress. Our findings may also provide a new strategy to improve plant adaptations to environmental changes via regulating plant cell wall synthesis.